Improving Student Learning Outcomes Using the Problem Solving Approach in Islamic Education Learning at SMP Negeri 5 Kampung Rakyat - Hatun, Hamdiah Fitro; Daulay, Muhammad Roihan (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
This study aims to improve student learning outcomes in Islamic Education using the Problem Solving Approach. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data for this study were obtained using test and observation techniques. Tests are used to improve student learning outcomes in developing a character of mutual respect and observation is used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that learning using the Problem Solving Approach can improve learning outcomes. This can be seen from the increase in the percentage of completeness of improving student ability results in each cycle with details of the pre-cycle 44.54%, the first cycle 79.57% and in the second cycle increased to 90.57%. Thus, learning using the Problem Solving Approach can be used as an alternative to improve student learning outcomes.